2012
DOI: 10.1029/2011wr011552
|View full text |Cite
|
Sign up to set email alerts
|

Exploring changes in the spatial distribution of stream baseflow generation during a seasonal recession

Abstract: [1] Relating watershed structure to streamflow generation is a primary focus of hydrology. However, comparisons of longitudinal variability in stream discharge with adjacent valley structure have been rare, resulting in poor understanding of the distribution of the hydrologic mechanisms that cause variability in streamflow generation along valleys. This study explores detailed surveys of stream base flow across a gauged, 23 km 2 mountain watershed. Research objectives were (1) to relate spatial variability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 38 publications
8
111
0
Order By: Relevance
“…During the recession period, the contributing areas contracted and only left main drainages and channel heads active. This is on accordance with empirical observations at TCEF that determined that topography drives hydrologic response during the melt period [e.g., Jencso et al, 2009;Jencso and McGlynn, 2011;Payn et al, 2012]. The good fit between the simulated and empirical connectivity duration curves furthermore exemplifies this.…”
Section: Internal Functioning and Structuresupporting
confidence: 72%
See 1 more Smart Citation
“…During the recession period, the contributing areas contracted and only left main drainages and channel heads active. This is on accordance with empirical observations at TCEF that determined that topography drives hydrologic response during the melt period [e.g., Jencso et al, 2009;Jencso and McGlynn, 2011;Payn et al, 2012]. The good fit between the simulated and empirical connectivity duration curves furthermore exemplifies this.…”
Section: Internal Functioning and Structuresupporting
confidence: 72%
“…This suggests increased recharge into the bedrock groundwater during the melt season and subsequent extended outflow during the growing season, thereby sustaining more elevated base flow in some of the TCEF subwatersheds. Jencso and McGlynn [2011] documented and Payn et al [2012] further suggested that the hydrologic controls on runoff at TCEF may shift from mainly topography-dominated flow during the snowmelt period to increasing groundwater contributions toward the end of the growing season and through the winter.…”
Section: The Evolution Of Variable Contributing Areasmentioning
confidence: 99%
“…3a and b) we find a high temporal variability within the spatial patterns of the catchment drainage system. This can be explained by specific discharge recessions for different landscape elements/hydrogeological storages during baseflow periods (Payn et al, 2012). The different subcatchments (or rather the areas connected to the drainpipes) show differences regarding their spatial extent, elevations and land use combinations.…”
Section: Nitrate Sourcesmentioning
confidence: 99%
“…Relative differences in Qsp among the basins, as well as the skew of the distribution of flow values, appeared to increase as conditions became drier, with a variation in unit area yield of three orders of magnitude at the driest conditions. This increasing 10 variability in yield among basins as flows decline has been observed elsewhere (Payn et al 2012, Shaman et al 2004, and attributed to the lessening role of topography and greater role of subsurface structure in determining flow volume as flows decline (Payn et al 2012, Shaw 2015.…”
Section: Temporal and Spatial Variability In Flowmentioning
confidence: 99%
“…It is also possible that the actual extent of the channel network has little effect on baseflow magnitude. If surface topography has a lessening influence on flow magnitude as conditions become drier (Payn et al 2012), greater subsurface storage capacity may be a more important factor than channel configuration and extent during the dry season. 20…”
Section: Basin Characteristics and Baseflows 20mentioning
confidence: 99%